Successful treatment of allergic conjunctival granuloma by topical tacrolimus: A clinicopathologic case report - Foroutan, Alireza (Indian J Ophthalmol, 2018)
Allergic conjunctival granuloma is a rare cause of conjunctival ocular lesions. The aim of this case report was to present a successful treatment of an allergic conjunctival granuloma with topical tacrolimus eye drops. A 20-year-old female presented with bilateral multiple yellow nodules of the bulbar conjunctival epithelium and conjunctival injection. The patient had tearing, photophobia, itching, foreign body sensation, and red eye. The patient's signs and symptoms progressed despite the use of topical steroids. The patient was treated by application of tacrolimus eye drop (0.005%) in her right eye every 6 h while the left eye was put on placebo. Her signs and symptoms were recorded at each visit. After 3 weeks' therapy with topical tacrolimus eye drop, the patient became asymptomatic in her right eye and conjunctival granulomas fully resolved. Topical tacrolimus seems to be an effective therapeutic option for the treatment of allergic conjunctival granulomas.